PERAN KEPEMIMPINAN KEPALA PERPUSTAKAAN DALAM PENGELOLAAN DAN PEMANFAATAN BUKU TEKS PELAJARAN DI SMK NEGERI 4 KOTA JAMBI - Gita Puspita Sari; Mohamad Muspawi; Musyaiyadah Musyaiyadah (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
Textbooks are essential learning resources that play an important role in supporting the teaching and learning process in schools. Effective management and utilization of textbooks require the leadership of the head librarian to ensure that their availability and use meet the needs of teachers and students. This study aims to analyze the leadership role of the head librarian in the management and utilization of textbooks and to identify the obstacles and efforts implemented at SMK Negeri 4 Kota Jambi. This research employed a qualitative approach with a case study design. Data were collected through interviews, observations, and documentation involving the principal, head librarian, library staff, teachers, and students. The findings revealed that the head librarian plays a significant role in planning textbook needs, coordinating procurement, managing inventories, supervising library services, and organizing borrowing systems. In terms of utilization, the head librarian encourages the use of textbooks as learning resources through lending services and collaboration with teachers. The obstacles identified include the limited number of textbooks, damaged book conditions, and inadequate coordination in procurement processes. Efforts undertaken include implementing a rotating borrowing system, maintaining book collections, and strengthening coordination with school stakeholders.